Analisis Kebutuhan Bahan Ajar Berbasis Kearifan Lokal Pesisir Pantai Pada Materi Hidrolisis Garam - Nur Faridatus So'imah; Fitria Fatichatul Hidayah; Eko Yuliyanto (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Chemistry learning that is taught today tends to only present concepts and formulas, as well as little practice so that students are less able to use the concepts that have been taught if they encounter problems in everyday life. The misconceptions that occur in the salt hydrolysis material are also assessed because there is no implementation of chemicals in everyday life. Therefore, the purpose of this study was to determine which teaching materials based on coastal local wisdom are suitable for use in salt hydrolysis materials. The type of research used is descriptive qualitative research. The research subjects in this study were prospective chemistry teachers. Based on the research conducted, it is obtained that the analysis results that the need for teaching materials that are in accordance with the characteristics of the respondents in the form of modules that can be used for independent study, the implementation of chemistry learning in everyday life can be done with an approach based on local wisdom (ethnoscience) by utilizing the local potential of coastal areas. and the local potential of the area that can be used as a source of learning material for salt hydrolysis is local salt. With this research, it is hoped that it can be used as a reference for further research by finding other more effective coastal local wisdom-based teaching materials.